Automated energy metering system - Drubo, Subir Mazumder; Dipti, Aysha Akter; Elma, Sayeda Sultana; Soailim, Hassan Sakeef (Brac University, 2023)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.